Adenosine plasma levels and adenosine receptor levels determine the outcome of adenosine test and head-up tilt test in syncopal patients with a normal heart. (14th October 2021) - Sotiriadou, M; Antoniadis, A; Vergopoulos, S; Konstantinidis, P; Bakogiannis, C; Karamanolis, A; Virgiliou, C; Gkika, E; Theodoridis, G; Mpalaouri, I; Mpougiouklis, D; Gerou, S; et al.
Abstract: Background/Introduction: The neurohumoral profile underlying the manifestation of reflex syncope remains incompletely understood. Adenosine plasma (ADP) and adenosine receptor (ADR) levels may differentiate the outcomes of head-up tilt table test (HUTT) and adenosine test (ADT) but their role in the diagnostic evaluation of patients with syncope has yet to be determined. Purpose: We sought to assess the ADP and ADR levels in patients without structural heart disease who underwent HUTT and ADT tests as part of the diagnostic workup of syncope. We specifically investigated differences in the outcomes of the HUTT and ADT tests as well as to the ADP levels during HUTT. Methods: HUTT and ADT were performed as per the standard protocols. ADT was considered positive in the event of asystole >6 seconds or heart block for >10 seconds after intravenous Adenosine 0.15 mg/kg administration in the supine position. ADP levels were assessed at three timepoints during the HUTT: at baseline (supine), immediately after bed tilt and, in cases of a positive HUTT, at the time of syncope. Patients were categorized in quintiles of very low, low, intermediate, high and very high baseline ADP levels. We also assessed the A2A ADR levels of monocytes. Results: We prospectively analyzed 124 patients (71 women, age 46.78±21.01 years). ADT was positive in 12.9% of patients and HUTT in 44.4% of patients. Patients with very low baseline ADP levels (lowest quintile) more frequently presented with a positive ADT (odds ratio [OR] 4.08, 95% Confidence Interval [CI] 1.40 to 13.13, p<0.05). Baseline ADP did not differ between patients with positive and negative HUTT. However, patients with vasodepressor response to HUTT exhibited increase in ADP from baseline to bed tilt (0.33±1.03 vs. 0.42±1.14 ppm/Um/L, p<0.05) and in syncope (0.70±1.89, P<0.05), while no difference was noted in patients with cardioinhibitory or mixed response. Patients with positive ADT and negative HUTT had higher ADR levels (221.5±88.56 MFI) as compared to patients with negative ADT and positive HUTT (59.78±83.65 MFI, p<0.05) and to patients with positive ADT and HUTT (33.29±35.77 MFI, p<0.05). Within patients with positive HUTT, those with onset of syncope in the Isoprenaline provocation phase (>20 min) had lower ADR levels (80.88±238.98 vs 89.43±96.08 MFI, p<0.05). Conclusion(s): Baseline ADP levels are related to the outcome of ADT while an ADP increase immediately after bed tilt and in syncope is evident in vasodepressor response to HUTT. Higher ADR levels are related to positive ADT and negative HUTT. Lower ADR levels are associated with more delayed onset of syncope during HUTT. ADP and ADR levels warrant further investigation as they may characterize a subset of patients with specific responses to ADT and HUTT and may be implicated in the pathophysiology of reflex syncope. Funding Acknowledgement: Type of funding sources: None.